Obesity Warning for Police Officers (JOURNAL OF SOCIAL SCIENCE RESEARCH, 2015)
Obesity Warning for Police Officers: Police officers are law-abiding citizens who wear a uniform to enforce the laws. They have the right to remain obese, but it can and will be used against them in the line of duty. This study discusses the need for police departments to institute programs that prepare and maintain healthy officers who can perform their jobs well throughout their careers. The study reveals the absolute need for police officers to be physically and mentally fit and argues that obese and unfit officers are dangers to themselves and to the public. Recommendations are made for police departments and officers to utilize in recruiting and training future officers and in educating veteran officers in order to maintain healthy and fit police officers. Although society is responsible for the kind of police it chooses to have, but policing is a physically demanding occupation and too important to be left to the unfit individuals.